PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP PENINGKATAN AKHLAK SISWA (Studi Survei di SMA Diponegoro 2 Jakarta) - Rizka Fajriah Anwar; Maria Ulfah; Kunaenih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research sets out to examine how far Islamic Religious Education (IRE) contributes to strengthening the moral conduct of students at SMA Diponegoro 2 Jakarta. It was prompted by an observable gap between the values conveyed in IRE classes and students' actual day-to-day behavior, including weak discipline, limited respect toward teachers, and recurring cheating. A quantitative, descriptive-analytical method was adopted, employing a cross-sectional design. Out of a population of 301 students, 75 respondents were selected through purposive sampling with the Slovin formula. Data collection combined a comprehension test on Fiqh of Worship to gauge the IRE variable (X) with a Likert-scale questionnaire to assess the Student Morals variable (Y), further supported by observation, interviews, and documentation. The Product Moment correlation technique was used for data analysis, yielding a correlation coefficient (rxy) of 0.415 a value that surpasses the r-table figures at both the 5% (0.227) and 1% (0.296) significance levels, leading to acceptance of the Alternative Hypothesis (Ha). The coefficient of determination (R Square) of 0.172 reveals that IRE accounts for 17.2% of the improvement in students' morals, while the remaining 82.8% stems from other factors such as family environment, peer relationships, and social media exposure. Overall, the findings point to a positive and significant relationship, falling within the moderate category, between IRE and the enhancement of students' morals at SMA Diponegoro 2 Jakarta. Keywords: Islamic Religious Education, Student Morals, Product Moment Correlation